A Feminist Analysis of Gender Inequality in Sally Nicholls’s Things a Bright Girl Can Do - Dhea Damayanti (Paradigma Lingua, 2025)
This study aims to depict the gender inequality experienced by the female characters in the novel. Gender inequality is discriminatory or different treatment received between men and women. Women are often seen as disproportionate to men and in a lower position, especially in education. In addition, gender inequality is still common and is the cause of women’s struggles. This study uses a qualitative method to reveal the problem, based on the theory of Simone De Beauvior (1953). The inequality experienced by female characters is have not chance to get the same rights as men in the form of education. This research concludes that women must do more in order to obtain their rights. In the novel, female characters must join a group of female fighters to defend their rights to get education and gain equality.